New algorithms for the split variational inclusion problems and application to split feasibility problems. (2nd December 2019) - Van Long, Luong; Viet Thong, Duong; Tien Dung, Vu
ABSTRACT: In this paper, we suggest two new iterative methods for finding an element of the solution set of split variational inclusion problem in real Hilbert spaces. Under suitable conditions, we present weak and strong convergence theorems for these methods. We also apply the proposed algorithms to study the split feasibility problem. Finally, we give some numerical results which show that our proposed algorithms are efficient and implementable from the numerical point of view.